Internationalisms and Lesser used Languages / Internationalismen und Kleinsprachen - Pöckl, Wolfgang (Kalbotyra, 2008)
Just as today’s major European languages gradually conquered domains in the early modern period that had previously been the preserve of Latin, it is now important for lesser used languages to establish themselves as – or to remain – instruments of communication in as many fields as possible. To do so, these languages must be subjected to a continuous process of modernisation at a variety of levels. Out of concern for the special character of their mother tongues, however, representatives of language preservation institutions often have fundamental objections to loan processes of all kinds, preferring instead to create new words out of native language material even though the native speakers themselves are reluctant to use them.The approach proposed in this article combines respect for the justified scepticism shown by speakers of lesser used languages towards the uncritical incorporation of elements from dominant neighbour languages and from today’s ubiquitous English on the one hand with a warning against the creation of insuperable barriers to the adoption of words and phrases (collocations, etc.) now in international use on the other. Especially “neutral” confixes of Greek or Latin origin (bio-, hydro-, agro-; -scope, -drome, -fer), for example, are well suited to the so-called process of modernisation, in the Indo-European languages at least. Similarly, phrases to be found in various languages that have been adopted as loan translations should not be automatically rejected as foreign bodies.For the necessary decisions to be taken on a rational basis, however, there is a need for much more intensive research into internationalisms than is currently available.